Muscle explosive power and foot-eye coordination of leg were studied as direct and concentration-mediated effects on shooting ability of young soccer players - M Yusuf Sulaiman; Ridho Bahtra; Syahrial Bakhtiar; Atradinal Atradinal (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This study examined the direct and indirect effects of leg muscle explosive power, eye-foot coordination, and concentration on the shooting ability of young soccer players. A correlational design with path analysis was employed. The participants were U-13 to U-17 players from SSB Binhar FC in Kerinci Regency, Indonesia. From a population of 55 players, 37 were selected through convenience sampling, and complete data were obtained from 28 players. Leg muscle power was measured using the Standing Broad Jump, eye-foot coordination with the Soccer Wall Volley Test, concentration through the Concentration Grid Test, and shooting ability using the Shooting Accuracy Test. Data were analyzed using SPSS 26 after normality, linearity, and multicollinearity assumptions were confirmed. The results showed that leg muscle explosive power (β = 0.067; p = 0.006), eye-foot coordination (β = 0.331; p = 0.046), and concentration (β = 0.196; p = 0.048) had significant positive effects on shooting ability. Concentration also partially mediated the relationship between leg power and shooting ability, as well as between eye-foot coordination and shooting ability, with an indirect effect of 0.121 for each path. Collectively, the three predictors significantly explained the variance in shooting performance (p < 0.001). In conclusion, shooting performance in junior soccer players is influenced by the integrated contribution of physical, coordinative, and psychological factors. Concentration plays a mediating role by directing physical and coordination abilities toward more accurate shooting execution. These findings support the implementation of integrated training programs combining physical conditioning, coordination drills, and concentration exercises to improve shooting performance in youth soccer players.